Molecular Phylogeny of the Cyrtophorid Ciliates (Protozoa, Ciliophora, Phyllopharyngea) - Gao, Shan (Public Library of Science, 2012)
Evolutionary relationships of cyrtophorian ciliates are poorly known because molecular data of most groups within this subclass are lacking. In the present work, the SS rRNA genes belonging to 17 genera, 7 families of Cyrtophoria were sequenced and phylogenetic trees were constructed to assess their inter-generic relationships. The results indicated: (1) the assignment of cyrtophorians into two orders is consistently confirmed in all topologies; (2) the order Dysteriida is an outlined monophyletic assemblage while Chlamydodontida is paraphyletic with three separate monophyletic families; (3) Microxysma, which is currently assigned within the family Hartmannulidae, should be transferred to the family Dysteriidae; (4) the systematic position of Plesiotrichopidae remains unclear, yet the two genera that were placed in this family before, Pithites and Trochochilodon, should be transferred to Chlamydodontida; (5) a new family, Pithitidae n. fam., based on the type genus Pithites was suggested; and (6) the sequence of Isochona sp., the only available data of Chonotrichia so far, is probably from a misidentified species. In addition, three group I introns of SS rRNA gene were discovered in Aegyriana oliva, among which Aol.S516 is the first IE group intron reported in ciliates.